The Effect of Accounting Knowledge, Business Scale, Age of Business and Organizational Culture on the Use of Accounting Information of UMKM with Moderate Environmental Uncertainty - Miftha Anasthasya Shintya Putri; Muhammad Aufa (Universitas Muhammadiyah Gresik, 2022)
his study aims to determine the effect of accounting knowledge, business scale, business age and organizational culture on the use of MSME accounting information by moderating environmental uncertainty. This type of research is a quantitative research. The sample of this research is business actors in Gresik City who are registered with the Cooperative Service and especially in the manyar and kebomas sub-districts, Gresik Regency. The technique used in this research is purposive sampling and obtained a sample of 116 respondents. The data used in this study is primary data in the form of a questionnaire. The analytical technique used is multiple linear regression analysis.The results showed that accounting knowledge, business scale and age of business had a positive effect on the use of accounting information for SMEs in Gresik City, while organizational culture had no effect on the use of accounting information for SMEs in Gresik City. Moderation regression analysis (MRA) shows that environmental uncertainty as a moderating variable can moderate accounting knowledge, business scale and organizational culture on the use of accounting information for SMEs in Gresik City. Environmental Uncertainty as a moderating variable cannot moderate the age of business on the use of accounting information for SMEs in Gresik City.